Maternal Mental Health and Child Dietary Diversity in Rural Kenya: Findings From a Pooled Analysis of 2 Baseline Studies - Md Abul Kalam; Juliet K. McCann; Zarmeen Shakil; Aishat Gambari; Michael Ochieng; Joshua Jeong (Current Developments in Nutrition, 2025)
Background: Most studies linking maternal mental health and child outcomes are from high-income countries and relatively few studies have explored how maternal mental health influences child nutrition in impoverished and rural settings across low-income countries. Objectives: This study aimed to assess the association between maternal mental health and child dietary diversity (CDD) in rural western Kenya. Methods: The analysis pooled baseline data from 2 RCTs of nurturing care interventions in rural western Kenya (clinical trial registrations are clinicaltrials.gov: NCT05796934 and clinicaltrials.gov NCT06165315, respectively). The 2 primary exposure variables were binary indicators for elevated maternal parenting stress and risk of maternal depression, which were self-reported using Parenting Stress Index—Short Form and Center of Epidemiologic Studies Depression Scale, respectively. The outcome was CDD, assessed using the World Health Organization measure for dietary diversity, which was based on maternal reports of the number of food groups consumed by the child in the past 24 h. Multivariable linear regression analyses were used to examine the association between maternal parenting stress, maternal depression and CDD. Results: The analytic sample was 690 mother–child dyads. The mean maternal age was ∼28 y (range: 17–49 y), whereas the mean child age was ∼14 mo (range: 6–25 mo). The mean dietary diversity score was 4.40 of 8 food groups. Approximately 20.14% of mothers had elevated parenting stress, whereas 41% were at risk of depression. The adjusted models showed that elevated maternal parenting stress was associated with lower CDD (β: −0.39, 95% CI: −0.80, 0.02; P = 0.059), whereas the association was not statistically significant between risk of maternal depression and CDD (β: 0.14, 95% CI: −0.14, 0.43; P = 0.323). Multiple sociodemographic factors were significantly associated with CDD. Children of mothers with higher social support, older children (range: 6–25 mo), and female children had higher dietary diversity. Meanwhile children from high food-insecure households had lower dietary diversity. Conclusions: These findings underscore the importance of integrating psychosocial components within child nutrition programs to address not only maternal mental health but also support the broader caregiving environment for families in low-and-middle-income settings like Kenya. Strengthening caregivers’ social support networks as part of these interventions may also have potential for promoting maternal mental health and children’s nutritional well-being.